Gamma Knife Radiosurgery for Primary and Secondary Trigeminal Neuralgia. (1st September 2019) - Gupta, Sunil K
Abstract: INTRODUCTION: Trigeminal neuralgia has always been a disease of conflict from pathological and management perspectives. Despite advances in the radiological imaging, evidence from autopsy studies, and intraoperative findings, concrete answers are not in sight. GKRS has been a strong contender among available treatment options for the management of trigeminal neuralgia. METHODS: All patients were evaluated on clinical criteria, BNI scale for intensity of pain, and facial hypoesthesia (if any) in a protocol-based manner. Only patients with BNI III to V were offered GKRS as a treatment modality. The Marseille point was targeted with a 70 to 90 Gy dose at 50% isodose. Patients were informed about all available treatment options with long-term prognosis and pain control rates. Patients in need of an immediate pain relief, in failed GKRS, and in a severe pain jeopardizing routine life and eating habits were not offered GKRS and were managed with microvascular decompression. RESULTS: A total of 108 (65 males, 43 females) patients received GKRS with the Perfexion model since 2009. Eighty-two percent of the patients received GKRS for primary trigeminal neuralgia, while the rest received GKRS for secondary trigeminal neuralgia due to skull base lesions (meningioma, schwannoma, cerebellar AVM, etc). A total of 78% of the patients had preoperative BNI scale IV, while 19% and 3% of the patients had grade III and V scale pain, respectively. Ninety-four percent patients gained BNI scale III intensity pain within 3 mo of GKRS. The 3-yr pain control rate (BNI I-II) could be attained in 81% of the patients. Twelve percent of the patients remained in BNI grade III. Two patients needed redo GKRS for their pain recurrence. CONCLUSION: It remains uncontested that MVD provides the best long-term pain-free control in patients of trigeminal neuralgia; however, GKRS remains a valuable feasible option for a selected group of patients. GKRS should be offered as an alternative treatment modality in patients not in urgent need of pain relief. In failed GKRS, authors did not encounter any difficulty in microvascular decompression.